Autophagy ATG16L1 rs2241880 impacts the colorectal cancer risk: A case‐control study. Issue 1 (11th December 2021) - Jamali, Leila; Sadeghi, Hossein; Ghasemi, Mohammad‐Reza; Mohseni, Roohollah; Nazemalhosseini‐Mojarad, Ehsan; Yassaee, Vahid Reza; Larki, Pegah; Zali, Mohammad Reza; Mirfakhraie, Reza
Abstract: Background: Despite many efforts to discover the important role of the autophagy process in the pathogenesis of colorectal cancer (CRC), the exact involved molecular mechanism still remains to be elucidated. Recently, a limited number of studies have been employed to discover the impact of autophagy genes' variants on the development and progression of CRC. Here, we evaluated the association between two single‐nucleotide polymorphisms (SNPs) in the main components of the autophagy genes, ATG16L1 rs2241880, and ATG5 rs1475270, and the CRC risk in an Iranian population. Methods: During this investigation, a total of 369 subjects, including 179 CRC patients and 190 non‐cancer controls have been genotyped using Tetra‐primer amplification refractory mutation system‐polymerase chain reaction (TP‐ARMS‐PCR) method. Result: The results demonstrated that the T allele of the ATG16L1 rs2241880 was significantly associated with the increased risk of CRC in the studied population (OR 1.64, 95% CI: 1.21–2.22, p = 0.0015). Moreover, ATG16L1 rs2241880 TT genotype increased the susceptibility to CRC (OR 3.31, 95% CI: 1.64–6.69, p = 0.0008). Furthermore, a significant association was observed under the recessive and dominant inheritance models ( p = 0.0015 and p = 0.017, respectively). No statistically significant differences were found in the ATG5 rs1475270 alleles and genotypes between the cases and controls. Conclusion: The results of the present study may be helpful concerning the risk stratification in CRC patients based on the genotyping approach of autophagy pathways and emphasize the need for further investigations among different populations and ethnicities to refine our conclusions. Abstract : Summary of the study.